Plan de negocio para la creación de un centro recreacional infantil, en el sector de La Aurora del cantón Daule - Carrillo Vera, Marcela Cristina (2023)
The proposal contained in this business plan is aimed at meeting the existing need for spaces for healthy and free recreation for children. It will include a stage of gathering information concerning the socio-family issue that allows us to define parameters to consider when proposing the location of the premises, its decoration and implementation of games and other necessary items to provide a quality service and according to user expectations. Although the main objective of the research work is aimed at infants, it is undoubtedly necessary to take into account the demands of their representatives, in this case we will address in the approach aspects such as easy access to the premises, proximity to the main places of care common, easy parking, publicity material; that is also informative, clear, precise and attractive to the public............